La resignificación del rol de género en mujeres que han sufrido violencia intrafamiliar entre 30 a 50 años, en el centro de equidad y justicia Quitumbe, desde abril a julio del año 2016 - Carrasco Solano, Ana Gabriela (2016)
The present systematization compile experiences of the group intervention project “The resignification of the gender role in women, who have suffered intrafamily violence between 30 to 50 years, in the center of Equity and Justice Quitumbe from April to July 2016”, Which was handled with a qualitative methodology, taking into account the role theory of the author Pichón Riviere and the need for this institution to expand its support network, which had a slight reception that was later strengthened and allowing more people to be Part of it. Therefore, the experiences, changes and modifications that were made when applied and the results at the end, were collected and ordered, in order to generate tools that facilitate the work in the area of psychology of this institution.